KEMİĞİ TUTAN BİR İNFEKSİYONDAN SCEDOSPORIUM INFLATUM (EŞEYLİ ŞEKLİ PSEUDALLESCHERİA BOYDİİ)'UN AYRILDIĞI BİR OLGU - YÜCEL, Ayhan; TUĞRUL, Murat; KANTARCIOĞLU, A. Serda; AYGIT, A. Cemal; ÖĞÜTLÜ, Aziz (Cerrahpaşa Medical Journal, 2014)
Background. Scedosporium inflatum is an anamorph of Pseudallerscheria boydii, a common saprobe found in soil. P. boydii is involved in causing a variety of infections elsewhere in the body including paranasal sinuses, eyes, joints, subcutaneous tissue, lung and brains and soft tissue infections. The infection is acquired by traumatic implantation of the organism into the skin and tissues. It is also the main cause of mycetoma and an agent of phaeohyphmycosis. Observation. A case of bone and soft tissue infection caused by S. inflatum, an anamorph of P. boydii is presented.